Computer literacy and the impact of health information systems on work and quality control in nursing practice - Aleksopulos, Hristos (Medicinski časopis, 2022)
Abstract Health information system includes a wide range of products, technologies and services suchas remote and mobile health technology, cloud-based services, medical devices, tele-monitoringdevices, assistive and sensor technologies, electronic health records, electronic medical records andother applications of information technologies in healthcare. Objective: To determine whether themethod of acquiring IT knowledge affects computer literacy and how the implementation of HIS affectswork and quality control. Methodology: The research was conducted as a cross-sectional study, in thepopulation of nurses. The sample consisted of 116 respondents, who voluntarily agreed to participatein the research. Results: Respondents who have formal education in informatics showed a higher levelof knowledge than respondents who do not. It was established that there is a statistically significantdifference in computer literacy between respondents who acquired IT knowledge in different ways.Those who rated themselves better have higher scores on the knowledge test. The data indicate theexistence of statistical significance of differences depending on the self-assessment of one's owncomputer skills. Almost half (46.7%) of respondents believe that the implementation of HIS made workeasier, while 26% of them believe that it had no impact on work or made work more difficult. Thelargest percentage (59.9%) of respondents believed that the health information system facilitatedquality control. Conclusion: The way of acquiring knowledge has the greatest influence on thecomputer literacy of nurses: nurses who had formal education showed a higher level of computerliteracy. Nurses believe that thanks to the implementation of HIS, the quality control of the providedservices has been significantly improved. The majority of health workers in the initial stages ofintroduction, application and development of the health information system had no formal education.Nevertheless, with the support of the institutions, they made a significant contribution to theimplementation of HIS in the Republic of Serbia.
Keywords: Health information system, implementation, information literacy, nurses